Dissociation culture, mind, and body (American Psychiatric Press, 1994)
Dissociation challenges many comfortable assumptions. Dissociative phenomena are often stark, extreme, and vivid. The identities of individuals with dissociation disorders shift between apparent opposites. Their pain is ignored. Trauma victims report floating above their injured bodies. Are these arcane, dramatic, or staged events, or does dissociation underlie some fundamental aspect of mental organization? Is dissociation the product of a troubled mind or a key to understanding the structure of consciousness and the mind-body relationship? Dissociation: Culture, Mind, and Body is the first book to combine cultural anthropology, cognitive psychology, neurophysiology, and the study of psychosomatic illness to present the latest information on the dissociative process. A variety of leading experts in each of these fields bring their knowledge on the unique role that dissociation plays in moderating social and psychological effects on the body. Dissociation: Culture, Mind, and Body is an invaluable resource for every student of dissociation and is designed for professionals in cross-cultural psychiatry and the influence of the mind on the body.